PERAN KEPOLISIAN DALAM MENERTIBKAN DAN MENGAMANKAN AKSI DEMONSTRASI - DUDY, ARYADI ALMAU; ASHADY, SUHEFLIHUSNAINI (Universitas Mahasaraswati K. Mataram, 2024)
Democracy is a symbol of modern civilization that guarantees the human rights of its citizens. Indonesia as a democratic country in article 28 of the 1945 Constitution guarantees the freedom of every citizen to express opinions in public, both in oral and written form, carried out in association and assembly. This is in line with Article 19 of the Universal Declaration of Human Rights, which states that everyone must not be interfered with in any way in seeking, receiving and conveying information and opinions. This research examines how demonstrations are regulated within the Indonesian National Police and how the police handle the perpetrators of demonstrations that end in anarchy. This research aims to better understand the role of the police regarding controlling and securing demonstrations that end in anarchy and to find out how to enforce the law against anarchic demonstrators. The research method used in this writing is normative legal research with a statutory and conceptual approach. Normative research is research whose object of study includes statutory provisions and their application to legal events. The research results showed that the police used Law Number 9 of 1998 and National Police Chief Regulation Number 7 of 2012 in handling demonstrations. Demonstrations that end in anarchy will be prosecuted through criminal law. The police do not tolerate demonstrators who disturb public order or endanger safety. Steps taken include investigation, prosecution and open trial